Uterine Rupture Secondary to Pyomyoma, Leading to Intra-Abdominal Abscesses following an Uncomplicated Vaginal Delivery - Rachel Hartman; Olga Colón-Mercado; Valario Johnson; James Baron; Lauren Davis (Case Reports in Obstetrics and Gynecology)
Background. Pyomyomas are an infrequent complication of uterine fibroids and, in extremely rare cases, the cause of spontaneous uterine rupture. A few documented cases were managed conservatively with oral antibiotics and CT-guided drainage or myomectomy with fertility preserved. However, treatment more frequently involves IV antibiotics and a hysterectomy. Case Description. A 31-year-old G2P0111 PPD 7 presented with intra-abdominal abscesses of unknown source. She was treated with broad-spectrum antibiotics, image-guided percutaneous (IR) drainage of the largest abscess, and surgical exploration with debridement. During surgery, she was diagnosed with spontaneous uterine rupture. The uterine defect was successfully repaired, and she was able to be successfully managed with fertility-sparing treatment. The patient ultimately did not require a hysterectomy. The final pathology was consistent with pyomyoma. Conclusion. In a majority of cases, pyomyoma treatment requires a hysterectomy, and fertility is unable to be preserved. However, conservative management with IV antibiotics, IR drainage, and surgical debridement could be a fertility-preserving approach to the treatment of pyomyomas.